Geopolitics, Theater, and Higher Education: Beginnings and Politicization of the School of Performing Arts, Universidad Nacional (UNA), Costa Rica - Rodríguez Jiménez, Edda E. (2025)
This article compiles some of the findings from the research on the processes of politicization within the School of Performing Arts at the National University. In addition to analyzing historical events, it also involves an approach from the perspective of institutionalization processes, which requires an evaluation of the forces in power and the influence of elites in 1970s Costa Rica. Elites operate within a specific socio-historical context to ensure the ideological sustenance of the system. This context allows, on the one hand, an analysis of politicization through the strategies of hegemonic sectors and their impact on the institution of higher education, and, on the other hand, the identification of how the National University, and specifically the School of Performing Arts, becomes established based on the foundations built by those in power and existing social contradictions. By determination, we refer to how higher education institutions are shaped according to the participation of individuals over an extended historical period, and how contradictions give rise to complex processes that leave a mark and reshape social structures, which are reproduced in a continuum, albeit not without nuances. To understand this process, it is essential to analyze it within a broader framework, which requires a geopolitical analysis to comprehend how Costa Rica, which gave birth to the National University, is situated in a world driven by deep contradictions.